Genome Segregation by the Venus Flytrap Mechanism: Probing the Interaction Between the ParF ATPase and the ParG Centromere Binding Protein - Caccamo, Marisa; Dobruk-Serkowska, Aneta; Rodríguez-Castañeda, Fernando; Pennica, Cecilia; Barillà, Daniela; Hayes, Finbarr (Frontiers in Molecular Biosciences, 2020)
The molecular events that underpin genome segregation during bacterial cytokinesis have not been fully described. The tripartite segrosome complex that is encoded by the multiresistance plasmid TP228 in Escherichia coli is a tractable model to decipher the steps that mediate accurate genome partitioning in bacteria. In this case, a ‘Venus flytrap’ mechanism mediates plasmid segregation. The ParG sequence-specific DNA binding protein coats the parH centromere. ParF, a ParA-type ATPase protein, assembles in a three-dimensional meshwork that penetrates the nucleoid volume where it recognizes and transports ParG-parH complexes and attached plasmids to the nucleoid poles. Plasmids are deposited at the nucleoid poles following the partial dissolution of the ParF network through a combination of localized ATP hydrolysis within the meshwork and ParG-mediated oligomer disassembly. The current study demonstrates that the conformation of the nucleotide binding pocket in ParF is tuned exquisitely: a single amino acid change that perturbs the molecular arrangement of the bound nucleotide moderates ATP hydrolysis. Moreover, this alteration also affects critical interactions of ParF with the partner protein ParG . As a result, plasmid segregation is inhibited. The data reinforce that the dynamics of nucleotide binding and hydrolysis by ParA-type proteins are key to accurate genome segregation in bacteria.